Hubungan Perhatian dari Orang Tua terhadap Hasil Belajar Siswa Sekolah Dasar - Tio Gusti Satria (Universitas Negeri Malang, 2021)
The purpose of carrying out this research is to determine the relationship between parental attention to the learning outcomes of class II SDIT Raudhatul Jannah Lubuklinggau. The research was using quantitative correlation by the sample of 55 students. Techniques in collecting data using questionnaires and documentation. Techniques in data analysis by applying the formula